2007
DOI: 10.1161/strokeaha.107.490292
|View full text |Cite
|
Sign up to set email alerts
|

Higher Total Serum Cholesterol Levels Are Associated With Less Severe Strokes and Lower All-Cause Mortality

Abstract: Background and Purpose-Evidence of a causal relation between serum cholesterol and stroke is inconsistent. We investigated the relation between total serum cholesterol and both stroke severity and poststroke mortality to test the hypothesis that hypercholesterolemia is primarily associated with minor stroke. Methods-In the study, 652 unselected patients with ischemic stroke arrived at the hospital within 24 hours of stroke onset.A measure of total serum cholesterol was obtained in 513 (79%) within the 24-hour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
86
3
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 42 publications
10
86
3
1
Order By: Relevance
“…3,4 Additionally, higher cholesterol levels have been associated with better short-term health outcome after stroke, including ICH. 5 However, most of these studies did not measure cholesterol fractions nor investigate whether HDL-C or LDL-C levels affected mortality or outcome. We studied the association between levels of LDL-C and mortality in ICH.…”
mentioning
confidence: 99%
“…3,4 Additionally, higher cholesterol levels have been associated with better short-term health outcome after stroke, including ICH. 5 However, most of these studies did not measure cholesterol fractions nor investigate whether HDL-C or LDL-C levels affected mortality or outcome. We studied the association between levels of LDL-C and mortality in ICH.…”
mentioning
confidence: 99%
“…They found a high mortality rate (p=0.002) and a poorer one month outcome (p<0.01) in correlation with low levels of total cholesterol. The association between low serum level of total cholesterol and worse outcome as well as with mortality rate was described also by Dyker et al in 977 patients [1997] and by Olsen et al [2007] when measuring the total cholesterol in 513 patients within 24 hour time window. The neurological score used for evaluation was the Scandinavian Stroke Score (SSS).…”
Section: Level Of Lipids During Acute Stroke As a Prognostic Marker Fmentioning
confidence: 74%
“…Furthermore, it has been shown that statins initiated before or immediately after ischemic stroke improved early and long-term survival and functional outcomes. 5 Second, higher serum total cholesterol and triglycerides are shown to be associated with better functional outcome and reduced long-term mortality after ischemic stroke, 3,4 but not with decreased risk for recurrent vascular events in the long term, which was the scope in our study. Third, our study included only patients with undetermined stroke etiology with no signs of smallvessel disease or any other probable or possible cause.…”
mentioning
confidence: 70%
“…3 Furthermore, an inverse relation between cholesterol and stroke severity and poststroke mortality has recently been reported, suggesting that higher cholesterol favors the development of small-vessel disease and therefore less severe strokes are associated with lower mortality. 4 Therefore, we question the usefulness and safety of long-term treatment with statins on all young patients with stroke of unknown etiology. Regarding cholesterol and outcomes after stroke, perhaps more is better.…”
mentioning
confidence: 99%